Studi Tematik Hadis Tentang Mendahulukan Yang Kanan Dalam Tinjauan Syar’i - Vina Rohmatika; Salim Rosyadi; Fajar Gilang Hermawan; Mochamad Miftahuddin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to provide and discuss the core themes of prioritizing the right in a syar'i review. This type of research method is a qualitative research method through a thematic approach, where this research is only focused on library research or library research and analyzing literature related to the theme. The results of the discussion of this study include general views regarding prioritizing the right in Islam, hadiths regarding prioritizing the right, as well as discussing core themes of prioritizing the right. The researcher concluded that it is important for someone to get used to it from an early age so that they always do good things by prioritizing the right side.